(untitled) (Research, Society and Development, 2021)
The objective of this work was to point out risks, laws, solutions, and strategies for the protection of Intellectual Property in Global Software Development in BRICS and to identify the bottlenecks of this service, with focus in this service in Brazil. The work was carried out in three stages: (a) a literature review was systematized on Global Software Development Offshore Outsourcing (DGSOO); (b) evaluation of legislation of personal data and software protection; (c) survey with specialists of the Information Technology companies in Brazil. Companies that operate offering this service are usually located in different countries with different law and procedures, and this makes the service of risk for intellectual property rights. The group BRICS is involved in this type of service. However, the challenge for this type of service is to maintain gains without losing the intellectual property rights protection. Due to the ubiquitous nature of software in today’s business environment, a DGSOO project needs to have its intellectual property protected, so that the risks of failure are minimized, and the benefits achieved. The greatest occurrences were found for the capacity to develop DGSOO projects and contracts, evidenced by the percentage of contracts finalized with delivery. Most contracts cover intellectual property clauses. The projects are mostly contracted in the software analysis stage and with confidential information, and yet 26.3% of contracts have problems with 1 to 10 projects per year; 5.3% have problems in 11 to 50 projects per year.